Pengembangan Sistem Informasi Manajemen Dalam Mendukung Transformasi Digital Dan Peningkatan Kinerja UMKM - Tri Djoko Santosa; Bangun Prajadi Cipto Utomo; Moh. Muhtarom (Shofanah Media Berkah, 2025)
Micro, Small, and Medium Enterprises (MSMEs) face significant adaptation challenges in the digital economy era, which demands integrated information management. This study aims to develop and examine the effectiveness of a Management Information System (MIS) in supporting digital transformation and improving MSME performance. The research employs a Research and Development (R&D) approach, with CV Pustaka Bengawan as the research object. Data were collected through observation, interviews, and questionnaires, while data analysis utilized descriptive statistics and paired sample tests. The results indicate that the implementation of the MIS has a positive and significant effect on business process efficiency and the quality of managerial information, which in turn contributes to improved MSME performance. This study concludes that an integrated MIS serves as a strategic foundation for supporting sustainable digital transformation in MSMEs.